The genome sequence of the tawny cockroach, Ectobius (Ectobius) pallidus (Olivier, 1789) [version 1; peer review: 2 approved] - Tony Hunter (Wellcome Open Research)
We present a genome assembly from a specimen of Ectobius pallidus (tawny cockroach; Arthropoda; Insecta; Blattodea; Ectobiidae). The assembly contains two haplotypes with total lengths of 2,087.55 megabases and 2,124.67 megabases, respectively. Most of haplotype 1 (98.55%) is scaffolded into 11 chromosomal pseudomolecules, while haplotype 2 is assembled to scaffold level. The mitochondrial genome has also been assembled and is 15.75 kilobases in length.